Efeito protetor da fração protéica do látex de Calotropis procera na mucosite intestinal induzida por irinotecano em camundongos - Bitencourt, Flávio da Silveira (2021)
Intestinal mucositis (IM) is a side effect of irinotecan (CPT-11), which is used for the treatment of colorectal cancer. The incidence of IM associated with severe diarrhea is estimated to be approximately 25% in patients. However, the clinical management of these side effects is still partially ineffective. Calotropis procera is a plant found in Africa, Asia, and South America. In Brazil, it is abundant in the northeast and has been shown to have antiinflammatory effects in animal models. The objective of the present study was to evaluate the antiinflammatory effect of a protein fraction of the latex of Calotropis procera in IM induced by CPT-11. Swiss mice (n = 8-12; 23 ± 2 g) were treated with saline (Sal; 5 ml/kg, i.p.) or CPT-11 (75 mg/kg, i.p.) for 4 days. In the other groups, the animals were given Calotropis procera (1, 5, and 50 mg/kg/day, i.v.) for 7 days, 30 min prior to CPT-11. On day 7, we evaluated diarrhea scores and the blood count of leukocytes and neutrophils ( 103/ml). In another experiment, we evaluated survival and body weight until day 12. After sacrifice on day 7, we collected the duodenum to determine myeloperoxidase (MPO) activity (neutrophils/mg of tissue) and perform microscopic (hematoxylin & eosin staining) and morphometric (villus/crypt ratio) analyses. Tumor necrosis factor  (TNF-), interleukin 1 (IL-1β; pg/ml; enzyme-linked immunosorbent assay), and in vitro contractions (i.e., percentage of contractions compared with 60 mM KCl) were also assessed. Immunohistochemistry was performed for cyclooxygenase 2 (COX-2), TNF-, IL-1β, inducible nitric oxide synthase (iNOS), and nuclear factor-B (NF-κB). The expression of iNOS was determined by Western blot. The statistical analyses were performed using analysis of variance followed by the Newman-Keuls or Kruskal Wallis/Dunn post hoc test. Values of p < 0.05 were considered statistically significant. Calotropis procera reduced diarrhea scores and MPO levels and improved survival at doses of 5 mg/kg (diarrhea: 1 [0-2]; MPO: 4.05 ± 1.07; survival: 75%) and 50 mg/kg (diarrhea: 1 [0-3]; MPO: 5.57 ± 1.50; survival: 75%) compared with CPT-11 (diarrhea: 3 [2-3]; MPO: 24.45 ± 3.0; survival: 47%). Calotropis procera reduced contractions (5 mg/kg: 165.1 ± 57.2) and the levels of the cytokines TNF- (5 mg/kg: 3.31 ± 3.0; 50 mg/kg: 9.79 ± 5.6) and IL-1β (5 mg/kg: 143.5 ± 41.5; 50 mg/kg: 182 ± 65.7) and increased the villus/crypt ratio (5 mg/kg: 2.79 ± 0.17) compared with the CPT-11 group (contractions: 906.1 ± 225.4; TNF-: 28.0 ± 3.5; IL-1β: 806.1 ± 247.6; villus/crypt ratio: 1.63 ± 0.17). Calotropis procera at doses of 5 and 50 mg/kg diminished the microscopic aspects of the duodenum (1 [0-2] and 1 [0-3], respectively) in animals with intestinal mucositis (4 [1-4]). Calotropis procera at a dose of 5 mg/kg reduced immunohistochemistry labeling for COX-2, TNF-, IL-1β, iNOS, and NF-κB and the expression of iNOS in the duodenum in animals with mucositis. However, Calotropis procera at any of the doses tested did not alter leukopenia, body weight, or the reduction of the number of neutrophils induced by CPT-11. These results suggest that the antiinflammatory and antidiarrheal effects of Calotropis procera are produced by the inhibition of inflammatory mediators that are important in CPT-11-induced intestinal mucositis.